Use of QRCode and Digital Signature Using The DSA Method to Authenticate Student Academic Documents - Suhardi, Suhardi (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
Verification of digital documents is no longer done conventionally but is also done digitally, such as signatures on documents. A signature is a means of authentic evidence as well as proving a person's identity, is a means of proving the authenticity or validity of an agreement or approval for something in a document issued by two or more parties so that it can be used as a solution to verify the integrity of valid data in a document. Application of signatures Digital is also commonly used at the North Sumatra Islamic University (UINSU) Medan, especially in student study documents. Even though UINSU Medan has implemented digital signatures, this application is still a signature image obtained through scanning or photos and manually inserted into a document so that other people can easily reuse the signature image and it can even be misused. To facilitate the digital signature process, the code generated from the signature formation process is entered into a QR code so that it is easy to use to carry out the electronic document authentication process. Researchers will use QR codes and digital signatures to authenticate student documents using the DSA method. This research will be implemented into an application model with PHP and MySQL programming. The student document authentication application model using the DSA method works well as evidenced by the QRCode which contains document token information which is different for each document so that it cannot be duplicated by non-owners of the document.